MENINGKATKAN KINERJA PELAYANAN PUBLIK : SISTEM TATA KELOLA PENDAFTARAN TANAH DI KANTOR PERTANAHAN KABUPATEN GORONTALO - Roni Abdullah (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
The land registration system in Indonesia plays an important role in managing natural resources and protecting land rights, which has a direct impact on the performance of public services. This research explores the performance of land registration at the Gorontalo District Land Office, with a focus on efforts to systematically increase land registration. Even though there have been good achievements in the land redistribution program and the unsystematic issuance of certificates, registration results still show less than optimal performance. The main problems include complicated bureaucracy, lack of human resources, and wrong public perceptions regarding proof of land ownership. The research method uses a qualitative approach with interviews with 15 key informants and 5 people who have registered land. The research results show that increasing socialization, employee training and proactive communication are very necessary to improve public service performance. Apart from that, management of community expectations must be considered so that the registration process is more efficient. With these steps, it is hoped that public confidence in the land registration system can increase, and legal certainty over land rights is guaranteed, which ultimately supports better public service performance in Gorontalo Regency.